Stability-indicating thin-layer chromatographic method for determination of darunavir in complex darunavir-beta-cyclodextrin in the presence of its degradation products - Kogawa, Ana Carolina [UNESP]; Mendonca, Jaqueline Nakau; Lopes, Norberto Peporine; Salgado, Hérida Regina Nunes [UNESP] (Royal Soc Chemistry, 2014)
Darunavir (DRV), a protease inhibitor used in the treatment of HIV infection, presents low water solubility and poor bioavailability. Therefore, the complexation of DRV with beta-cyclodextrin (beta-CD) was performed. This drug is not described in official compendiums. A simple, selective and inexpensive stability-indicating thin-layer chromatographic (TLC) method for the determinations of DRV in complex DRV-beta-CD and its degradation products was developed. The TLC method employs aluminum plates precoated with silica gel 60(F-254) as the stationary phase and purified water and methanol, 70 : 30 (v/v) adjusted to pH 2.4 with glacial acetic acid as the solvent system to provide spots for DRV (R-f = 0.66) and its degradation products in acidic (R-f = 0.73 and 0.76), basic (R-f = 0.53) and oxidative (R-f = 0.71, 0,75 and 0.84) media. The chromatogram was visualized in a UVA chamber at 365 nm. HPLC analysis was performed on a Waters HPLC system, Phenomenex CN Luna (250 x 4.6 mm) column and mobile phase consisting of water + 0.1% glacial acetic acid and acetonitrile + 0.1% glacial acetic acid in the ratio 60 : 40 (v/v) at a flow rate of 1.0 mL min(-1) and 268 nm for the separation of DRV (t(R) = 7.3) and its degradation products in acidic (t(R) = 5.1 and 6.7 min), basic (t(R) = 7.8 min) and oxidative (t(R) = 5.1, 5.5 and 6.7 min) media. DRV-beta-CD was subjected to acid and alkali hydrolysis and oxidation and analyzed by the proposed methods in the presence of its degradation products, which were identified by LC-MS. As the methods could separate DRV from the degradation products, these techniques can be employed as indicative stability methods and can be effectively applied in quality control of DRV complexed to beta-CD.